Analysis of trends and variability in frequency and intensity indices of precipitation over Myanmar during 1985-2020 - Min Khaing; Win Win Zin; Zin Mar Lar Tin San; Soe Thiha; Manish Shrestha (Innovation in Engineering, 2025)
In this study, an analysis of long-term extreme precipitation indices was conducted using daily observation data from 38 stations in Myanmar spanning from 1985 to 2020. Three frequency indices and six intensity indices of precipitation were analyzed using RClimDex software. The Mann-Kendall test, along with Sen’s slope method, was employed to determine the trends and magnitude of extreme indices. The spatial distribution patterns varied across different physiographic regions, with 63% to 76% of the stations displaying increasing trends in various indices. The consecutive dry days showed increasing trends in the hilly regions, whereas the consecutive wet days exhibited decreasing trends in those areas. For the maximum 1-day precipitation, 45% of stations displayed increasing trends, with 5% of those being statistically significant. The Western Hilly Region exhibited rising trends in extremely wet days, whereas other regions have experienced mixed trends. These findings highlight the need for adaptive water resources engineering and management to address the localized changes of precipitation trends that affect floods and droughts in Myanmar.